2021
DOI: 10.1016/j.sjbs.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Addition Oats (Avena sativa) and Cinnamon on Cookies and their Biological Effects on Rats Treated with Cirrhosis by CCL4

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The amount of nutrient constituents that exist in the lactose-free milk powder falls within the range mentioned in earlier studies [ 24 , 25 ]. The percentage range of each constituent present in the oat powder was also reported in previous studies [ 26 , 27 , 28 ], and our results are concordant with their results. The nutrient compositions of the mushroom powder and jaggery were almost similar to the results of Farzana [ 29 , 30 , 31 , 32 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The amount of nutrient constituents that exist in the lactose-free milk powder falls within the range mentioned in earlier studies [ 24 , 25 ]. The percentage range of each constituent present in the oat powder was also reported in previous studies [ 26 , 27 , 28 ], and our results are concordant with their results. The nutrient compositions of the mushroom powder and jaggery were almost similar to the results of Farzana [ 29 , 30 , 31 , 32 ].…”
Section: Resultssupporting
confidence: 94%
“…This could be due to the high oat-to-mushroom powder ratio in MOS 1, as oats have a higher carbohydrate content than mushrooms ( Table 2 ). Krishnamoorthy et al [ 31 ] reported that there is 41.6% of carbohydrates in mushrooms, and Aly [ 26 ] reported that there is 66.89% of carbohydrates in oats. Similarly, in Table 2 , it is shown that the carbohydrate content of oats is higher than that of mushrooms, indicating that our findings are consistent with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The microscopic appearance of liver tissue from healthy rats (T-) presents a normal physiological appearance with well-structured and delineated centrilobular veins, biliary ducts, and portal spaces. Several studies that focused on the histological study of rat liver tissue presented the same aspect [83][84][85].…”
Section: Histological Studymentioning
confidence: 98%
“…The results indicated that the addition of sprouted oats powder reduced the in vitro starch digestibility. In addition, Aly et al (2021) added oats and cinnamon to cookies to improve their quality. Therefore, it is feasible to add functional natural substances to baked products to enhance their nutritional value and lower their postprandial glycaemia.…”
Section: Introductionmentioning
confidence: 99%